Optimization of Biodiesel Synthesis from Avocado Seeds Using Response Surface Methodology (RSM) - Nicander, Priscillia stevanies; Muljani, Srie; Darma, Apriandi Putra (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
The synthesis of biodiesel from avocado seed oil has been successfully conducted. This study aimed to determine the optimized parameters for the transesterification reaction using Response Surface Methodology (RSM). The transesterification reaction was carried out with variations in the methanol mole ratio of 1:4, 1:6, and 1:8 at temperatures of 40 C, 50 C, and 60 C, utilizing 1 wt% KOH relative to the oil. The avocado seed oil, obtained from the extraction process, has a free fatty acid content of 1.95%. The RSM results indicated that the optimized parameters for biodiesel production were at a temperature of 60 C with a methanol mole ratio of 1:6. The final yield achieved was 82%, calculated based on the initial weight of the oil. The biodiesel produced had a cetane number of 75, a density of 877.4 kg/m, and a viscosity of 4.768 cSt. These values meet the SNI standards, which require a minimum cetane number of 51, a density of 850890 kg/m, and a viscosity of 2.36 cSt.